Education opportunities for women: The case of Latin America and the Caribbean - Schiefelbein, Ernesto
Education has reached a balance in opportunities for access by men and women to the various education levels. Reaching this balance has probably been one of the greatest achievements of Latin American and Caribbean education systems as a whole, during the latter part of the 20th century. Population censuses in the 1980s confirm not only the disappearance of major sex differences in schooling levels observed in the fifties, but that the opposite exists in half the countries where women have gained an edge in access to primary and secondary schooling, although they still have to obtain that equality in higher education. School enrollment in the 1990s permits one to declare that the trend towards equality in education opportunities for women is being maintained in the region. Schooling data are corroborated by those on literacy. Lastly, fragmentary information permits one to assert that women are also making good use of education opportunities in terms of academic achievement and grades passed. This evidence is important both for the overall analysis of education development in the region and for specific policy design
Keywords: Gender analysis